Creative industry: Music industries subsector in Indonesia - Alexandri, Mohammad; Arifianti, Ria; Kostini, Nenden; Fordian, Dian (Technium Social Sciences Journal, 2021)
The objective of this research are : 1. How is the development of the creative industry in the music sub-sector? 2. How is the SWOT analysis of the creative industry in the music sub-sector? Research method is descriptive qualitative methods. The result of this research is with the SWOT analysis available, the music industry in this digital era has both positive and negative things that can be considered by a music production team. Recommendation of the study is This royalty issue will harm musicians because they cannot enjoy the four rights that should be obtained, namely the right to reproduction, the right to copy the original copyrighted work; desirous rights, commonly used for advertisements, trailers, films; distribution rights, the exclusive rights of the copyright holder to distribute their copyrighted works; and performing rights, exclusive rights obtained by the owner of the work to broadcast, play, and display his song to the wider community.